2011
DOI: 10.1007/s13105-011-0109-z
|View full text |Cite
|
Sign up to set email alerts
|

The physiology of the normal human breast: an exploratory study

Abstract: The physiology of the nonlactating human breast likely plays a key role in factors that contribute to the etiology of breast cancer and other breast conditions. Although there has been extensive research into the physiology of lactation, few reports explore the physiology of the resting mammary gland, including mechanisms by which compounds such as hormones, drugs, and potential carcinogens enter the breast ducts. The purpose of this study was to explore transport of exogenous drugs into ductal fluid in nonlac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Identifying the underlying cause of these different NAF colors in healthy women may explain our findings. We hypothesize that several potential factors may contribute to NAF color such as diverse cellular [54] or bacterial [55] compositions in NAF samples, nutrients and proteins [56][57][58], medications [59][60][61][62] or food intake [62][63][64][65][66][67][68]. But studies addressing the association between these possible factors and color classes are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the underlying cause of these different NAF colors in healthy women may explain our findings. We hypothesize that several potential factors may contribute to NAF color such as diverse cellular [54] or bacterial [55] compositions in NAF samples, nutrients and proteins [56][57][58], medications [59][60][61][62] or food intake [62][63][64][65][66][67][68]. But studies addressing the association between these possible factors and color classes are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Breast milk is a valuable medium for exposure monitoring because it can be collected noninvasively at substantial volume, the high fat content captures lipophilic compounds, and it reflects exposures to young women and infants. Other matrices that can be used for biomonitoring include fine-needle aspirates of breast ductal fluid (Mills et al 2011), hair (e.g., Bessette et al 2009), adipose tissue (e.g., Covaci et al 2002; Dewailly et al 1999; Falk et al 2012), saliva (e.g., Bessette et al 2010), exhaled breath (e.g., Cope et al 2004; Plebani et al 1999), and fingernails (Esteban and Castaño 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Extensive experimental procedures performed in human mammary glands can be challenging and sometimes almost impossible [25]. Even with these limitations, we are able to provide an alternative to understanding how the toxins get into the breast milk.…”
Section: Multi-layer Modelmentioning
confidence: 99%
“…Our approach is that it will provide an alternative to estimate the milk to plasma ratio (M/P ratio) for breastfeeding women. Research publications have shown that toxins are able to penetrate the epithelial layers and get into the breast milk in higher concentrations compared to the resting mammary gland [6,8,9,11,12,[25][26][27][28][29][30]. This work takes into consideration the particle size and properties of the layers to estimate the percentage of toxins that are introduced into the breast milk.…”
Section: Multi-layer Modelmentioning
confidence: 99%